Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 1968–1986 - Arsenault, Mathieu; Martel, Marcel (Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 2017)
Les gains en matière de soins de santé mentale en français arrivent au compte-goutte entre 1968 et 1986. L'État ontarien agit avec prudence dans ce dossier. Malgré les pressions des individus et de l'Association canadienne-française de l'Ontario, la mise en place de soins de santé mentale en français s'est butée à de nombreux obstacles tels que la pénurie de personnel parlant français, les difficultés à attirer ce personnel et à les inciter à demeurer notamment dans le Nord, les carences du système d'éducation à former des francophones, les hésitations du gouvernement ontarien, mais aussi l'hostilité au fait français.

Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)

Profil santé des communautés francophones en situation minoritaire au Canada [infographie] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Are there mental health differences between Francophone and non-Francophone populations in Manitoba? - Chartier, Mariette Jeanne; Finlayson, Gregory; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; Walld, Randy; De Rocquigny, Janelle (The Canadian Journal of Psychiatry, 2014)
Objective: Francophones may experience poorer health due to social status, cultural differences in lifestyle and attitudes, and language barriers to health care. Our study sought to compare mental health indicators between Francophones and non-Francophones living in the province of Manitoba. Methods: Two populations were used: one from administrative datasets housed at the Manitoba Centre for Health Policy and the other from representative survey samples. The administrative datasets contained data from physician billings, hospitalizations, prescription drug use, education, and social services use, and surveys included indicators on language variables and on self-rated health. Results: Outside urban areas, Francophones had lower rates of diagnosed substance use disorder (rate ratio [RR] = 0.80; 95% CI 0.68 to 0.95) and of suicide and suicide attempts (RR = 0.59; 95% CI 0.43 to 0.79), compared with non-Francophones, but no differences were found between the groups across the province in rates of diagnosed mood disorders, anxiety disorders, dementia, or any mental disorders after adjusting for age, sex, and geographic area. When surveyed, Francophones were less likely than non-Francophones to report that their mental health was excellent, very good, or good (66.9%, compared with 74.2%). Conclusions: The discrepancy in how Francophones view their mental health and their rates of diagnosed mental disorders may be related to health seeking behaviours in the Francophone population. Community and government agencies should try to improve the mental health of this population through mental health promotion and by addressing language and cultural barriers to health services.

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Les disparités d'accès aux soins de santé parmi la minorité de langue officielle au Québec - Falconer, James; Quesnel-Vallée, Amélie (Recherches sociographiques, 2014)
Cette étude examine l’effet de l’aptitude en français sur la santé et sur les besoins de soins de santé non satisfaits au Québec, en utilisant un modèle multiple de régression logistique. Nos résultats indiquent que les anglophones unilingues du Québec sont 26 % plus susceptibles que les anglophones bilingues à se déclarer en mauvaise santé. Théoriquement, ce mauvais état de santé devrait mener à une utilisation accrue des soins de santé. Cependant, malgré leur mauvais état de santé, les anglophones unilingues sont 52 % plus susceptibles de déclarer des besoins en soins de santé non satisfaits. Ces disparités dans l’état de santé ainsi que dans l’accès aux soins de santé s’expliquent par l’aptitude à s’exprimer en français. Par ailleurs, ces effets ne sont pas modifiés par l’inclusion de variables potentiellement confondantes telles que les caractéristiques sociodémographiques et socioéconomiques. Les résultats suggèrent que ce sont les politiques visant à réduire les obstacles à l’accès aux soins de santé des populations minoritaires qui pourraient améliorer l’accès aux soins, et, éventuellement, la santé des anglophones unilingues du Québec. Mots-clés : populations minoritaires de langue officielle, anglophones, Québec, utilisation des services de santé, inégalités de santé, accès aux soins de santé

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Peut-on parler d'une déshospitalisation des services ? Les soins en santé mentale de la minorité de langue officielle dans le Nord-Est ontarien - LeBel, Marie (La fin de l'asile ? Histoire de la déshospitalisation psychiatrique dans l'espace francophone au xxe siècle, 2018)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Expérience de conciliation travail-famille de parents francophones de la région d’Ottawa : étude pilote - Moreau, Denise; Polomeno, Viola; Ranger, Marie-Christine (Reflets, 2018)
Plusieurs études soutiennent que l’expérience de la conciliation travail-famille (CTF) a un impact majeur sur la santé et la qualité de vie des familles (Winter, et collab., 2006). Les objectifs de cette étude pilote étaient les suivants : 1) documenter l’expérience de la CTF chez un groupe de parents francophones de la région d’Ottawa, 2) élaborer, pré-tester et administrer le questionnaire sur l’expérience de conciliation travail-famille (ECTF), et 3) exécuter les premières étapes de validation de cet instrument. Cet article présente les données recueillies auprès de 46 participantes et participants concernant leurs expériences et leurs stratégies de CTF ainsi que leurs suggestions pour favoriser la CTF. Mots-clés : conciliation travail-famille, parents, francophones, étude pilote, Ottawa

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Ciel éclairci ! Vers un meilleur accès aux services de santé mentale et de lutte contre les dépendances en français en Ontario - Programme de soutien au système provincial (Centre de toxicomanie et de santé mentale, 2018)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Santé mentale en français. Comprendre les enjeux et l’urgence de collaborer aux TNO - Réseau TNO Santé (Comprendre les enjeux et l’urgence de collaborer aux TNO, 2018)

Enquête sommaire sur la santé des francophones de Colombie-Britannique - RésoSanté Colombie-Britannique (2016)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

La recherche en santé et en services sociaux auprès des populations francophones en situation minoritaire au Canada. Revue de littérature et analyse des thèmes de recherche (2014-2016) - Sauvageau, Marie-Michèle (Association des collèges et universités de la francophonie canadienne, 2018)

Santé des francophones et utilisation des services de santé dans les Réseaux locaux d’intégration des services de santé d’Érié St.Clair et du Sud-Ouest - Smith, Michaela (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2013)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.